BALOK PELAT BERDINDING PENUH (GIRDER PLATE BEAM) - Rusman Asri (UNIVERSITAS INDO GLOBAL MANDIRI, 2018)
Steel construction work generally requires a maximum power that can be retained by a cross-section of the burden, so for that we need a large enough cross-section to carry the load. In an attempt to overcome this problem, created a new profile as needed, so that the use of a cross-section Walled Beams Plates Plates Full or often called Girder (Girder Plate). Fully walled plate girder is a beam with a high cross-section, so it is probably influenced by the folding wings on plate element or the element plates bend the body, so that the necessary calculations to solve the folding and buckling. To overcome this happens folding or bending, buckling calculations required lokak (local buckling) and if it is necessary, then the component mounted stiffeners (stiffener), Bearing stiffener, Intermediate stiffener, and Longitudinal stiffener. To meet the needs of the beams to support the existing load, so he found a full-walled beam size plate (Plate Girder) d = 1,400 mm high, with a weight plate size 15 mm x 1350 mm, and the wing plate size 25 mm x 500 mm of steel fy = 240 MPa. Beam stiffeners fitted pedestal (Bearing stiffener), stiffeners between (Intermediate stiffener) and longitudinal stiffeners (stiffener Longotudinal).Keywords: girder plate, local buckling, stiffener